Efforts to Foster a Young Entrepreneurial Spirit at SMK Tunas Harapan Batang Serangan, Langkat Regency - Harianto, Adi; Mhd Restu Razaq; Manda Dwipayahi Bhastary; Mega Sanjaya; Kuandi Chandra; Darwan Tanady; Robin; Irwadi; Rusdiana Br Simamora; Dewi Rapiah Pakpahan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Digital technology is indispensable and vital nowadays. The swift advancement of information technology in today's globalized society necessitates that individuals possess the capability to effectively employ technology. This is equally pertinent to the younger generation or students. Educational institutions must combine entrepreneurial education with digital technology into their curriculum and include components of extracurricular activities. This community service initiative involves Tunas Harapan Vocational High School as the partner. Additionally, the challenge within this community service involves fostering student enthusiasm for engaging in business activities or entrepreneurship, educating SKM Tunas Harapan students on utilizing the Canva digital platform for commercial purposes, and offering training to enable students to design for entrepreneurial or business endeavors. The training session had 10 students and 2 instructors as participants. Moreover, the training techniques employed in this community service initiative include lectures, question-and-answer sessions, debates, demonstrations, and hands-on practice. The outcomes of the exercise demonstrate that students at Tunas Harapan Vocational School have improved their knowledge and abilities.